Implementation of the Development of the School-Level Curriculum (Ktsp) in Senior High Schools for Islamic Religious Education Subjects - Dayun Riadi; H. Hery Noer Aly; Liqfa Nurul Fadhila; Muhammad Dicky Khoirullah; Katronaldo Pratama (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The 2006 Curriculum, published by the Ministry of National Education beginning in the 2006/2007 academic year, was introduced under the name KTSP (Education Unit Level Curriculum). The 2006 Curriculum empowers teachers to create grounded learning concepts tailored to the needs and conditions of their schools.